Efektivitas Bukaan pada Rumah Bandayo Pobo’ide Terhadap Kenyamanan Fisiologis - Rahmayanti; ST Haisah (Jurnal Teknik, 2020)
Bandayo Pobo'ide is one of the traditional houses in Indonesia that uses natural ventilation as a physiological cooling. Nowadays, Bandayo Pobo'ide houses are used only for traditional ceremonies. In the past, the houses were used both for residence as well as for conducting traditional ceremonies. This affects the need for natural ventilation in the house. The role of openings is a major factor in providing physiological comfort in space. The percentage of openings that can accommodate the comfort of the room is 40% of the total wall area. This study aims to evaluate the effectiveness of openings for current activities. Field measurements were carried out to determine the phenomena in and around Bandayo Pobo'ide. Descriptive method was used to explain the effectiveness of the opening against the physiological comfort which will be calculated based on WSC (wind support comfort). The results showed that the openings were less than 40%, therefore the wind speed inside the building was relatively stagnant at 0.1m/s.